Blind Estimation of the Phase and Carrier Frequency Offsets for LDPC-Coded Systems. (1st December 2010) - Imad Imad, Rodrigue Rodrigue; Houcke Houcke, Sebastien Sebastien; Ghogho Ghogho, Mounir Mounir
Abstract : We consider in this paper the problem of phase offset and Carrier Frequency Offset (CFO) estimation for Low-Density Parity-Check (LDPC) coded systems. We propose new blind estimation techniques based on the calculation and minimization of functions of the Log-Likelihood Ratios (LLR) of the syndrome elements obtained according to the parity check matrix of the error-correcting code. In the first part of this paper, we consider phase offset estimation for a Binary Phase Shift Keying (BPSK) modulation and propose a novel estimation technique. Simulation results show that the proposed method is very effective and outperforms many existing algorithms. Then, we modify the estimation criterion so that it can work for higher-order modulations. One interesting feature of the proposed algorithm when applied to high-order modulations is that the phase offset of the channel can be blindly estimated without any ambiguity. In the second part of the paper, we consider the problem of CFO estimation and propose estimation techniques that are based on the same concept as the ones presented for the phase offset estimation. The Mean Squared Error (MSE) and Bit Error Rate (BER) curves show the efficiency of the proposed estimation techniques.